2004
DOI: 10.1111/j.1364-3703.2004.00257.x
|View full text |Cite
|
Sign up to set email alerts
|

Two chorismate mutase genes from the root‐knot nematode Meloidogyne incognita

Abstract: SUMMARY Parasitism genes encoding secretory proteins expressed in the oesophageal glands of phytoparasitic nematodes play critical roles in nematode invasion of host plants, establishment of feeding sites and suppression of host defences. Two chorismate mutase (CM) genes potentially having a role in one or more of these processes were identified from a Meloidogyne incognita oesophageal gland-cell subtractive cDNA library. These M. incognita enzymes (designated as MI-CM-1 and MI-CM-2) with amino-terminal signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 35 publications
0
55
0
4
Order By: Relevance
“…Among these 232 effector-like proteins, we found 42 previously reported RKN effectors, including SXP/RAL-2 like proteins [16], Venom Allergen-like Proteins (VAP) [17], Chorismate mutases [18], Cathepsin L-like protease 1 (MiCpl1) [19] as well as 32 plant cell wall-degrading enzymes, encompassing cellulases, xylanases, pectate lyases and expansin-like proteins [20]. Finding previously known and characterized Meloidogyne effectors among our list of predicted effectors constituted an important validation of our approach.…”
Section: Resultsmentioning
confidence: 98%
“…Among these 232 effector-like proteins, we found 42 previously reported RKN effectors, including SXP/RAL-2 like proteins [16], Venom Allergen-like Proteins (VAP) [17], Chorismate mutases [18], Cathepsin L-like protease 1 (MiCpl1) [19] as well as 32 plant cell wall-degrading enzymes, encompassing cellulases, xylanases, pectate lyases and expansin-like proteins [20]. Finding previously known and characterized Meloidogyne effectors among our list of predicted effectors constituted an important validation of our approach.…”
Section: Resultsmentioning
confidence: 98%
“…Mj-FAR-1 was shown to promote giant cells and nematode development when expressed in planta (Iberkleid et al, 2013). Similarly, secreted proteins homologous to plant chorismate mutases have been characterized in RKN (Doyle & Lambert, 2003;Huang et al, 2005). Chorismate mutase overexpression in planta altered root growth and it has been suggested that this effector affects the auxin pool within host cells.…”
Section: Nematode Effectors Affecting Defence Responsesmentioning
confidence: 97%
“…Several different plant nematode groups including cyst nematodes, RKNs and migratory endoparasites such as P. coffeae (Doyle and Lambert, 2003;Haegeman et al, 2011a;Huang et al, 2005b;Jones et al, 2003;Lambert et al, 1999;Long et al, 2006;Lu et al, 2008;Vanholme et al, 2009b) produce chorismate mutases (CM) as part of their effector complement. Chorismate mutase is a key regulatory enzyme in the shikimate pathway in plants and bacteria and the fact that no other enzymes from this pathway are present in PPNs strongly indicates a role in the host plant.…”
Section: Suppression Of Host Defencesmentioning
confidence: 99%